Personnel management - Croft, Arthur C.; La Plante, John J. (New York : Alexander Hamilton Institute, 1964)
The book deals with people, their direction and motivation. It covers what are considered to be the best practices in the fields of training, employee relations and management development, as well as the methods that should be used to develop a productive employee relations program.
Personnel management in a people business: 27 p.
Includes index.
ne 13/07/2018
Loans
Keywords: Personnel management